Infestation by Pediculus humanus (Anoplura: Pediculidae) in a metropolitan area of Southeastern Brazil - Linardi, Pedro Marcos (1998)
Adults, nymphs and nits of the Pediculus humanus were found in a frame-house infesting the clothes and bedding of three inhabitants in a shanty town in S. Paulo county, S. Paulo State. A total of 198 nits were found glued in 15.0 cm² of fibres of the infested clothing, giving a ratio of 13.2 nits/cm². Having in view that the precarious living conditions, promiscuity, absence of basic sanitation and negligence of the sanitary authorities in various Brazilian cities, this situation should not be underestimated. This find should be more frequent than an isolated observation.